2012
DOI: 10.1002/pat.3073
|View full text |Cite
|
Sign up to set email alerts
|

OCVD polymerization of PEDOT: effect of pre‐treatment steps on PEDOT‐coated conductive fibers and a morphological study of PEDOT distribution on textile yarns

Abstract: The functionalization of textile fibers with intrinsically conductive polymers has become a prominent research area throughout the world. A number of coating techniques have already been utilized and optimized to get the uniform layers of conductive polymers on the surface of different substrates. In our previous study, we produced poly(3,4‐ethylenedioxythiophene) (PEDOT)‐coated conductive fibers by employing oxidative chemical vapor deposition (oCVD) technique. This paper describes the effects of pre‐treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 32 publications
1
19
0
1
Order By: Relevance
“…The current paper is the continuation of our previous research work in which functionalization of viscose and polyester yarns with PEDOT polymer through VPP process was studied . It was revealed that both viscose and polyester were successfully coated with PEDOT and exhibited quite good conductivity values.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…The current paper is the continuation of our previous research work in which functionalization of viscose and polyester yarns with PEDOT polymer through VPP process was studied . It was revealed that both viscose and polyester were successfully coated with PEDOT and exhibited quite good conductivity values.…”
Section: Introductionmentioning
confidence: 68%
“…16 The current paper is the continuation of our previous research work in which functionalization of viscose and polyester yarns with PEDOT polymer through VPP process was studied. [30][31][32] It was revealed that both viscose and polyester were successfully coated with PEDOT and exhibited quite good conductivity values. However, viscose fibers lost mechanical properties significantly after PEDOT coating whereas polyester retained its virgin properties.…”
Section: Introductionmentioning
confidence: 99%
“…Usually, the CVD process is used to coat the small pieces of substrates, due to which, in our previous experiments (19)(20)25) , we were able to produce only 15 cm long fibers. However, in the present research work, we have made a hundred fold scale increase and prepared 15 m long PEDOT-coated viscose and PES conductive fibers.…”
Section: Resultsmentioning
confidence: 99%
“…Viscose and polyester fibers were coated with PEDOT polymer by using CVD process, which was optimized in our previous research (25) . In CVD process, the fibers were first treated with an oxidant (FeCl 3 ) solution in 1-butanol followed by subsequent drying.…”
Section: Polymerization Of Edot To Pedot On the Surface Of Textile Fimentioning
confidence: 99%
See 1 more Smart Citation